Altered Complexity of Spontaneous Brain Activity in Schizophrenia and Bipolar Disorder Patients. Issue 2 (11th July 2021) - Zhang, Nan; Niu, Yan; Sun, Jie; An, Weichao; Li, Dandan; Wei, Jing; Yan, Ting; Xiang, Jie; Wang, Bin
Abstract : Slice images of the brain regions with significant difference Slice images showed the differences of (a) the effect of group and (b) the effect of interaction between the control and patient groups after adjusting for age, sex, and education (P < 0.05, GRF corrected). CAL.L: Calcarine fissure, DCG.L: Median Cingulate, LING.L: Lingual Gyrus, PCUN.L: Precuneus, IOG.R: Inferior Occipital Gyrus, MTG.R: Middle Temporal Gyrus, HIP.R: Hippocampus, THA.R: Thalamus, MFG.R: Middle Frontal Gyrus, MTG.L: Middle Temporal Gyrus by N. Zhang et al (586–595)